If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -3g = 14 Solving 35 + -3g = 14 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -3g = 14 + -35 Combine like terms: 35 + -35 = 0 0 + -3g = 14 + -35 -3g = 14 + -35 Combine like terms: 14 + -35 = -21 -3g = -21 Divide each side by '-3'. g = 7 Simplifying g = 7
| 3y=-2x+2 | | .50x=1500 | | 8x-3=4x+39 | | -70+2x+8x=70 | | (2y+20)= | | f(x)=x^2+11x+0 | | 63x-35= | | 3x^2-2x-100=0 | | r^16+5=11 | | 45x=25-5y | | 4x+3y=y+8 | | -4n+16=116 | | 2100=x*60 | | 5y=25-45x | | 2h(4h+3)= | | 18y-18=18 | | -w^7-2=19 | | log(x+6)=log(8x)-log(3x+2) | | 6x+10+4x+40=180 | | 4n+16=116 | | 2y+10-y=-7 | | -(2-3b)=2(3b-4) | | 4n+16=16 | | 4(2x-y)+11=8x-13 | | 3a+5=2a+17 | | 6x+19=-30 | | 3x-9=5x+15 | | 14x-9=21+4x | | 3t+4t=51-8 | | (-5)+4=x-3 | | 3(u+3)=-6(4u-1)+9u | | (6x+40)-2x=(2x+116)-2x |